O muro na materialização, na expressão, na relação, de um domínio, de um jogo - Maria Ana de Paiva Sousa Santos (2020)
The wall can be presented as a primary device for defining architectural space. Motivated by the feeling of the growing enclosure of interior spaces, the accentuated individuality - and through searching for encouraging solutions - a reflection is given on the wall's role when defining the architectural space. From its understanding as a limit to the necessity and pertinence of its presence, we intend to explore this device's potential and its contribution to a greater or lesser relation and articulation of spaces. Through four fields of study, we propose a reflection that covers different but complementary components, which aim to enrich the experience of architecture and contribute to the project 'to be realized', in 'my' pursuit as an architect. First of all, a personal exhibition of the academic path that notifies the problem of the wall; then a theoretical position based on various authors who study the composition and organization of the space; a third vision, cultural and anthropological, that reminds us that architecture is made of people and for people and depends on the environment in which it's inserted; finally, the analysis of concrete works, seeking different languages for the same problems.